Penerapan Konsep Edukatif pada Perencanaan Dan Perancangan Fasilitas Penunjang Agrowisata Aren di Karangasem - I Kadek Wahyu Maharta; Agus Kurniawan; Anak Agung Gede Raka Gunawarman (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Agro-tourism is a type of tourism activity that utilizes the potential of nature, farming (agriculture), culture and rural community activities as a tourist attraction, with the aim of enriching insight, experience, amusement parks and rural agro-industry business relations. Karangasem Regency is a region of Bali that plays an important role in agriculture and plantations, which can be developed as an agricultural tourism area. Karangasem is an area with natural advantages in terms of land suitable for plants and people who like gardening. In addition, Karangasem Regency offers views of extensive agricultural land and plantations, where many of these agricultural lands and plantations are overgrown with palm trees. Aren (Arenga pinnata Merr.) is a multipurpose plant that has long been known as an industrial raw material. Almost all the physical and productive parts of this plant can be utilized and have economic value. Karangasem Regency is the third province in Bali with the highest production of Jaka/Aren Trees. To take advantage of all the potential that exists in Manggis Village, Manggis, Karangasem, a place for education, processing, recreation, and sale of processed palm sugar is needed, which collaborates aspects of tourism, agriculture, with knowledge, which is called aren agro-tourism.